Study on Nutrient Balances of Newly Developed Lowland Rice Fields at Kleseleon Village, Malaka District, Nusa Tenggara Timur - -, Sukristiyonubowo -; Riyanto, Damasus (JOURNAL OF TROPICAL SOILS, 2020)
The land allocated for newly opened lowland rice can be from ultisols, oxisols, inceptisols, and potential acid sulfate soils. The study was aimed to evaluate nitrogen (N), phosphorous (P), and potassium (K) inputs â€“ outputs of newly developed lowland rice under different treatments and to validate the N, P, and K recommended applications rate according to N, P, and K balances. The study was conducted in Kleseleon village, Malaka District. Five treatments were tested namely T0: farmers practices, T1: NPK at recommendation rate + Rice straw compost, T2: NPK at recommendation rate + Smart + Rice straw compost, T3: Â¾ NPK at recommendation rate + Smart + Rice straw compost, and T4: NPK at recommendation rate + Smart + Rice straw compost. The treatments were arranged in a randomized complete block design with three replications. The nutrient balances were constructed according to the difference between nutrient inputs and losses. The results indicated that there were surplus N, P, and K across the treatments and more than adequate to replace N, P, and K removed by harvest products. The suggested N, P, and K application rates were 100 kg urea, 100 kg SP-36, and 100 kg KCl with the addition of compost 3 Mg ha-1 season-1.